School Environmental Project: Educational Device in the Shaping of Environmental Subjectivities - Galindo-Quiroga, Claudia (2024)
This documentary research develops a study on the School Environmental Projects Program (PRAE), focusing on its theoretical and pedagogical aspects, and its influence on the formation of environmental subjectivities in the school context. The article advocates for a critical interpretation of environmental education from the principles of ecological ethics and political ecology. It problematizes the instrumental, extractivist, and conservationist approaches that have historically predominated within the field. In methodological terms, the research adopted a framework of documentary analysis, with a dual hermeneutic-emancipatory interest, and divides its structure into two complementary parts: the development of an analytical review on the institutional emergence of the PRAE under educational policies of Decree 1743 of 1994 and the National Policy of Environmental Education of 2004. This constitutes a prelude to the critical evaluation of its qualities and gaps in terms of its capacity to agency ecological subjects. It also explores the pedagogical potential of the categories of subjectivity and experience, as possible catalysts for a transcendental and meaningful environmental education through the PRAE.